A history of the Smithsonian American Art Museum : the intersection of art, science, and bureaucracy - Fink, Lois Marie (University of Massachusetts Press, 2007)
"Dedicated to the art of the United States, the Smithsonian American Art Museum contains works by more than 7,000 artists and is widely regarded as an invaluable resource for the study and preservation of the nation's cultural heritage. But as Lois Marie Fink shows in this probing narrative, the history of the museum is hardly one of steady progress. Instead, it reads like a nineteenth-century melodrama, replete with villains and heroes, destruction by fire, dashed hopes, and periods of subsistence survival - all leading eventually to a happy ending." "In recounting the history of the museum from 1846 to 1980, Fink unravels the various levels of institutional authority, power, governance, and bureaucracy and shows how people at each level influenced the fortunes of the collection. She also places changing concepts of art and museum practice in the context of national ideals and Washington realities."--Jacket